Public Policy Failure: A Study of Home Industry Food Production Certification Policy - Hendri Koeswara; Desna Aromatica; Malse Yulivestra; Muhammad Ichsan Kabullah; Roza Liesmana (Jurnal Public Policy, 2021)
There is an increasing concentration of Public Administration scientists on measuring whether policy succeeds or fails. It is no longer clear how best to ensure that the policy process from formulation to policy implementation is the best and more effective way. Including in the Home Industry Food, Production Certificate Policy (SPP-IRT) is taken as a locus. Study of the Home Industry of Ground Coffee in Nagari Koto Tuo, Tanah Datar Regency. The policy on offering SPP-IRT has undergone several changes, but it will not be effective. It will fail to provide quality assurance and food safety.  the increase in IRTPs who have certificates does not increase. The research method used in this study uses a qualitative approach with a case study research design. The results showed that providing Food Home Industry Certification (IRTP) with the case in the provision of IRTP Coffee Powder certificates in Nagari Koto Tuo showed that the policy failures included tolerable policy criteria. Modest loss when it happens does not fundamentally hold back the goals the proponents want to achieve, and the minor opposition and criticism that occurs is almost non-existent in this SPP-IRT-related policy.